The Link Between Ferroptosis and Cardiovascular Diseases: A Novel Target for Treatment - Hu, Huilin; Chen, Yunqing; Jing, Lele; Zhai, Changlin; Shen, Liang (Frontiers in Cardiovascular Medicine, 2021)
Ferroptosis is an iron-dependent cell death, which is characterized by iron overload and lipid reactive oxygen species (ROS) accumulation. Ferroptosis is morphologically, biochemically, and genetically distinct from apoptosis, necrosis, autophagy and other forms of cell death. Ferroptosis is regulated by a variety of factors and controlled by several mechanisms, including mitochondrial activity and metabolism of iron, lipid and amino acids. Accumulating evidence shows that ferroptosis is closely associated with the pathophysiological processes of a variety of cardiovascular diseases (CVDs), including cardiomyopathy, myocardial infarction, ischemia/reperfusion injury, heart failure and atherosclerosis. This review summarizes the current status of ferroptosis and discusses ferroptosis as a potential therapeutic target for CVDs.